Urgensi Pos Bantuan Hukum (Posbakum) Dalam Pemenuhan Hak Terdakwa Di Rutan Boyolali - Kurnianingsih, Marisa; Iksan, Muchamad; Kuntoro, Cahyo; Sartanto, Alfath (Fakultas Hukum Universitas Mulawarman, 2023)
Indonesia is a state of law, but many people do not comply with the law. In 2018–2020, the number of crimes in various regions of Indonesia continues to increase, and Boyolali Regency is no exception. This means that many people who act as perpetrators of criminal acts have to deal with the legal process. With so many people becoming defendants, the state has an obligation to ensure that the rights of the accused are fulfilled, one of which is the right to get free legal assistance through the presence of Posbakum both at detention centers and at the District Court. However, many defendants did not know or use their rights. This study used a qualitative, non-doctrinal approach by seeking informants to find out about the role of Posbakum and efforts to optimize Posbakum in the Boyolali detention center. From this research, it will be known that Posbakum has a role in fulfilling the rights of the accused during the process of dealing with the law and the efforts made by the Boyolali detention center in realizing the rights of the accused who are undergoing detention there.